Sequencing batch reactor combined with coarse filter for domestic wastewater treatment - Maatoq, Hameedah M.; Al-Rekabi, Wisam S.; Abbas, Sarmad A. (International Journal of Engineering and Technology, 2022)
SBR is a system of treatment that relies on activated sludge and consists of a group of processes occurring in the same tank to obtain a wastewater treatment. In this study, the SBR combined with the filter has been applied to treat domestic wastewater in Basra city. The treat-ment unit consists of a domestic wastewater collection tank (250 L), an SBR tank with dimensions of (60x50x30) cm. this tank contains a mixer, diffuser for aeration, and an open hole at a height of (0.15 cm) for the discharge of treated water to the filter which consists of tank (60x70x30) cm. and two layers of gravel, the first layer with a diameter (2/5 – 6/5) mm. and the second layer with adiameter (6/5 – 9/5) mm. with the thickness of 7cm for each layer. The results of removal pollutants for domestic wastewater (COD, BOD, PO4, SO4, and NO3), for SBR alone, were (93%, 93%, 52%, 10, and 65%) respectively and for SBR combined with filter for the same pollutant, the removal values were as follows (97%, 96%, 56% 29%, and 70%) respectively.